Krivdna in objektivna odškodninska odgovornost delodajalca - Končina Peternel, Mateja (Delavci in delodajalci, 2014)
The primary function of the Tort Law is a fair distribution of the damage risk and the secondary, its prevention. So an employer%s strict liability should only apply if there is sufficient causal link between the damage and the dangerous work. The employer should also be liable for fault when he failed to devise a safe system of work providing for an obvious danger. With fair apportion of the responsibility for the loss between the employer and the employee, the courts can strengthen the preventive conduct of both of them.
Keywords: delodajalci; odgovornost; odškodninska odgovornost; osebna odgovornost; sodna praksa; zaposleni